Ergonomics study on workers in electrical industry by using simulation analysis - Nurul Husna, Zakaria (2018)
Ergonomics has improved the scope on safety and minimized risk at the workplace by looking into possible factors affecting product quality, work performance, and machine efficiency. According to research and statistics nowadays, there has been a cumulative concerns in quality, health and safety requirements in numerous professions and it is difficult to overlook the issues related to ergonomics risk. The most common risks identified for work are awkward posture, contact stress, wrist injury, static posture, body fatigue, twisted spine and over bending due to too far and unreachable object. Thus, this study aims to observe, investigate and analyze a working area and the workers in the manufacturing industry by using lean and ergonomic tools. The methods used are by using the Witness Simulation Software, manual Rapid Upper Limb Assessment (RULA) and RULA in Delmia Simulation Software. Based on collecting data on workers’ performance obtained from the actual manufacturing environment, simulations of these workers and statistical analysis of 23 people will be analyzed. By using the result from the first step of analysis, the sample size is reduced to 9 workers and being reduced again to 3 workers. This method will validate this finding and evaluate the exposure of individual workers to ergonomic risk factors associated with upper extremity and whole body postural. Based on the result, three workers from different processes have been selected: Toroidal Winding’s worker, Epoxy worker, and VMI worker. Those that have been selected for the simulation are experiencing MSDs risk at different level, with a score of 6, 6 and 4 by using Delmia simulation and 7, 6, and 3 by using manual assessment. By looking at the result, the relation to workers’ performance and MSDs did have a relation, but need to look at another aspect such as workload of each worker as well.